Intellectual Capital Dimensions and Profitability of Sharia Banking in OIC Countries - Falikhatun Falikhatun; Siti Mudrikah (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2022)
Sharia banks typically have two primary objectives: commercial and social. To fulfill their commercial mission, sharia banks must generate profits as it is one of the most important metrics used to evaluate long-term competitiveness and ensure their operational sustainability. This paper intends to delve deeper into the impact of intellectual capital dimensions on the profitability ratio of Sharia banking. Using panel data from 34 companies from 2015 to 2019, this study distinguished between fixed and random effects using the Hausman test. The Return on Assets (RoA) is then utilized as a proxy for the profitability ratio. Utilizing samples of sharia banking institutions from OIC countries such as Indonesia, Malaysia, Bangladesh, and Pakistan, we found a positive relationship between intellectual capital dimensions and the profitability ratio. Human capital and structural capital have a partial impact on profitability, while relational capital has no influence on the profitability of sharia banks in OIC-member countries.======================================================================================================== ABSTRAK – Dimensi Modal Intelektual dan Profitabilitas Bank Syariah di Negara-negara OKI. Bank syariah umumnya memiliki dua tujuan utama, yaitu komersial dan sosial. Untuk menjalankan misi komersialnya, bank syariah perlu menghasilkan laba yang merupakan salah satu indikator kunci yang digunakan untuk menilai daya saing jangka panjang dan memastikan keberlanjutan operasionalnya. Tulisan ini bertujuan untuk menggali lebih dalam pengaruh dimensi modal intelektual terhadap rasio profitabilitas bank syariah. Dengan menggunakan data panel dari 34 perusahaan mulai tahun 2015 hingga 2019, penelitian ini menggunakan uji Hausman untuk membedakan efek tetap dan efek acak. Return on Asset (RoA) digunakan sebagai proksi untuk rasio profitabilitas. Adapun sampel dalam penelitian ini adalah bank syariah dari negara-negara anggota OKI seperti Indonesia, Malaysia, Bangladesh, dan Pakistan. Temuan kami mengungkapkan bahwa secara statistik terdapat pengaruh positif signifikan antara dimensi modal intelektual dengan rasio profitabilitas. Dikaji secara parsial, hanya modal manusia dan modal struktural yang berpengaruh, sedangkan modal relasional tidak berpengaruh terhadap profitabilitas bank syariah di negara-negara anggota OKI tersebut.